Curbing Power or Progress? Governing with an Opposition Veto - Albrecht Morgenstern (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
Veto institutions are often dominated by government opponents with rival electoral and policy interests (e.g. government"). I investigate the tradeoff between policy control and policy blockade when both the government and the veto party may cater to opposing special interests. The value of an opposition veto depends on whether electoral accountability can discipline bad type politicians. When this is not the case, a veto is beneficial only if the government's special interests are expected to be harmful. In contrast, when bad types care about (re-)election, a veto always increases expected welfare, providing a new rationale for the frequent occurrence of "divided government". Without policy rivalry, an opposition veto fares even better.
Keywords: D72; A12; H11; D78; 330; Political Accountability; Opposition; Veto; Divided Government; Veto; Politische Entscheidung; Ökonomische Theorie der Demokratie; Interessenpolitik; Spieltheorie; Wohlfahrtseffekt; Theorie